2013
DOI: 10.1016/j.enbuild.2013.02.021
|View full text |Cite
|
Sign up to set email alerts
|

Experimental investigation of convective heat transfer during night cooling with different ventilation systems and surface emissivities

Abstract: a b s t r a c tNight-time ventilation is a promising approach to reduce the energy needed for cooling buildings without reducing thermal comfort. Nevertheless actual building simulation tools have showed their limits in predicting accurately the efficiency of night-time ventilation, mainly due to inappropriate models for convection. In a full-scale test room, the heat transfer was investigated during 12 h of discharge by nighttime ventilation. A total of 34 experiments have been performed, with different venti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(10 citation statements)
references
References 20 publications
0
9
0
1
Order By: Relevance
“…亓晓琳等人 [34,35] [36] 搭建了一个全尺寸实验房间用以对比研究置换通风 和混合通风两种夜间通风模式, 开发了一种可以应 用于建筑设计初期估算夜间通风制冷性能的图表. Dréau等人 [37] 在此基础上进行了多种工况的实验, 对 [40] . 同时, 基于相关研究, 刘加平等人 [41] [42] .…”
Section: 夜间通风的气候适宜性unclassified
“…亓晓琳等人 [34,35] [36] 搭建了一个全尺寸实验房间用以对比研究置换通风 和混合通风两种夜间通风模式, 开发了一种可以应 用于建筑设计初期估算夜间通风制冷性能的图表. Dréau等人 [37] 在此基础上进行了多种工况的实验, 对 [40] . 同时, 基于相关研究, 刘加平等人 [41] [42] .…”
Section: 夜间通风的气候适宜性unclassified
“…Chao and Hu [16] discussed that classroom occupants can be exposed to harmful concentrations because emissions may accumulate without proper ventilation during the unoccupied periods. Earlier research shows that night ventilation has been typically used to enhance indoor thermal conditions [17][18][19][20][21][22]. Even though many standards and guidelines have been provided for health-based ventilation [10,23,24], different night ventilation methods have been relatively rarely studied regarding organic pollutant levels in the mornings at the beginning of space use.…”
Section: Introductionmentioning
confidence: 99%
“…The results showed that the higher the cooling demand of the building, the higher the potential contribution of night ventilation under specific boundary conditions. In Le Dréau et al [17], heat transfer during 12 h of discharge by nighttime ventilation in a full scale test room was investigated. Different ventilation types, air change rates, temperature differences between the inlet air and the room, and floor emissivity were examined.…”
Section: Night Ventilationmentioning
confidence: 99%